Stimulating Namibian learners' democratic participation and leadership in a senior primary rural school: a participatory action research study - Kaongo, Trofimus Shipena (Rhodes University, Faculty of Education, Department of Secondary and Post School Education)
This study investigates the democratic participation and leadership opportunities of primary school learners within the Namibian education system, as outlined in the Basic Education Act. 3 of 2020. While the Act emphasises the involvement of secondary school learners in decision making, primary school learners are largely overlooked. Despite policies recognising children as democratic participants in education, implementation remains inconsistent, with secondary school learners often restricted to tokenistic leadership roles. To address this imbalance, the study explores leadership opportunities for primary school learners, seeking to understand the underlying factors contributing to the gap in democratic leadership at the primary school level. Grounded in a critical paradigm, this qualitative research draws upon Kurt Lewin's field theory and theory of change, using participatory action research (PAR) to promote transformation. The research followed a two-phase design. In phase 1, data was collected through individual interviews with teachers and focus group discussions with learners. Phase 2 adopted PAR to assess how engaging learners in the research process stimulated democratic participation and leadership development. Data were gathered through reflective journals maintained by both the learners and the researcher. Abductive analysis of the data, informed by Lewin's theoretical framework, the Lundy model of participation, Hart's ladder of participation and leadership theory, revealed varying understandings of democratic participation among participants. For many, it was equated with learners' freedom of expression, collective decision making and leadership autonomy. However, while learners were afforded opportunities to lead school-initiated activities such as cleaning campaigns, sports events and class monitoring, their involvement in the initiation of these activities remained limited. The study found that learner leadership could be significantly enhanced through greater involvement in collective decision making, motivation and recognition by teachers, and increased leadership autonomy. Nonetheless, barriers such as age differences, peer pressure, limited time and teachers' negative attitudes impeded the realisation of these objectives. The study contributes significant insights into learner leadership in Africa, particularly in the under-researched context of senior primary school leadership. It highlights the need for greater equity in leadership opportunities between primary and secondary learners and advocates a transformative school environment that fosters multiple leadership pathways based on individual cognitive development.
Keywords: Student participation in administration-- Namibia; Democratic participation; Participatory action research; Education, Elementary-- Namibia; Agent (Philosophy)